PERAN PRICE DISCOUNT MEMODERASI PENGARUH PRODUCT KNOWLEDGE DAN CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION - Rismawan, I Made Ari; Purnami, Ni Made (E-Jurnal Manajemen; Vol 6 No 1 (2017), 2017)
The research has purpose to determine role of price discount in moderation effect of product knowledge and celebrity endorser on purchase intention. This research was in Denpasar City with 170 respondents as sample, purposive sampling method and dispersed using questionnaire with criteria that have been adjusted. The analysis technique used is moderation regression analysis. The results indicated product knowledge had significant and positive effect on purchase intention, means higher product knowledge then increase purchase intention. Celebrity endorser didn’t has significant effect on purchase intention, meaning someone who has high product knowledge tends to ignore celebrity endorser related purchase intention. Price discount moderate weaken effect of product knowledge on purchase intention, meaning someone who has high product knowledge tends have doubts to buy related product quality such as product defects and durability of  product. Price discount can significantly moderate but meaningless because celebrity endorser didn’t has significant effect on purchase intention.
Keywords: price discount; product knowledge; celebrity endorser; purchase intention